Wages, housework, and attitudes in the Philippines - Connie B. Dacuycuy (Philippine Institute for Development Studies (PIDS), 2016)
This paper is one of the few studies that systematically analyze housework in the Philippines. It seeks to understand how wage and attitudes to work and family life affect the time devoted to housework. Based on different specifications and estimators, our findings indicate that the respondent's own wage is not a significant predictor of his or her housework hours, but it is a significant predictor of the spouse's time devoted to nonmarket production. We find that the husband's housework hours are positively affected by the female respondent's wage while the wife's housework hours are negatively affected by the male respondent's wage. We turn to the Philippine context to explain these results and find the combination of egalitarian society and gender inequality in the labor market as plausible explanations. Results also show that both wage and attitudes have direct effects on the wife's housework time but that some of the effects of wage are mediated by the respondent's attitudes toward gender roles.
Keywords: D13; J22; 330; Housework; Wage; Specialization; Instrumental Variable Technique; Philippines